Review of Lessons from exceptional language learners who have achieved nativelike proficiency: Motivation, cognition and identity by Zoltán Dörnyei and Katarina Mentzelopoulos - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2023)
Let me start this review by saying that it is a huge privilege to be able to review the book co-authored by the late Zoltán Dörnyei, a scholar who not only managed to put the countries of Eastern and Central Europe on the map of research into individual difference (ID) factors in the realm of second language acquisition (SLA) but in many ways shaped and spearheaded the development of such research.